2017
DOI: 10.21037/jtd.2017.11.60
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of video-assisted thoracic surgery with open surgery in the treatment of ectopic mediastinal parathyroid tumors

Abstract: Background: To investigate the therapeutic effect of different surgical treatment for ectopic mediastinal parathyroid tumors and pathological features.Methods: A total of 21 patients who were diagnosed with ectopic mediastinal parathyroid tumors and underwent surgeries in our department from May 1995 to May 2015 were collected and retrospectively analyzed.Results: Twenty-one patients including 8 female (36.4%) and 13 male (63.6%) were collected. Among these patients, 9 cases were treated with video-assisted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The literature review identified nine English‐language case series consisting of five or more VATS parathyroidectomies, with a combined total of 87 patients ( Table ). PHPT was the most common pathology treated (51 of 69), and 54 per cent of patients (34 of 63) had undergone previous non‐curative neck exploration, consistent with the present patient group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature review identified nine English‐language case series consisting of five or more VATS parathyroidectomies, with a combined total of 87 patients ( Table ). PHPT was the most common pathology treated (51 of 69), and 54 per cent of patients (34 of 63) had undergone previous non‐curative neck exploration, consistent with the present patient group.…”
Section: Resultsmentioning
confidence: 99%
“…Video‐assisted thoracoscopic surgery (VATS) for ectopic mediastinal parathyroid adenoma was first described over 20 years ago, but significant experience has been acquired only in centres performing large numbers of parathyroidectomies. It is an attractive approach for appropriately selected patients, with literature suggesting a shorter hospital stay and lower complication rates. National Institute for Health and Care Excellence (NICE) guidelines note that there are limited published data on VATS parathyroidectomy, and recommend the procedure should be performed only in specialist units with a multidisciplinary team.…”
Section: Introductionmentioning
confidence: 99%
“…Approaches to the thymus include median sternotomy, lateral thoracic thoracotomy, mediastinoscopy, manubriotomy, cervical collar incision, and thoracoscopic surgeries using the lateral and subxiphoid approaches. Recently, thoracoscopic surgery using the lateral thoracic approach has become the primary option for minimally invasive surgery (2)(3)(4)(5)(6)(7)(8). However, intercostal neuralgia is a common complication associated with thoracoscopic surgery performed using the lateral thoracic approach (12).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical approaches for mediastinal tumors include median sternotomy, lateral thoracotomy, mediastinoscopy, manubriotomy, transcervical incision, and thoracoscopic surgery using the lateral and subxiphoid approaches. Currently, thoracoscopic surgery using the lateral thoracic approach is the most common procedures (2)(3)(4)(5)(6)(7)(8). We have been performing multi-port mediastinal tumor resection using the lateral thoracic approach since 2008 and single-port mediastinal tumor resection using the subxiphoid approach since 2011 for mediastinal tumors (9).…”
Section: Introductionmentioning
confidence: 99%